Engineered composite tissue as a bioartificial limb graft. (August 2015) - Jank, Bernhard J.; Xiong, Linjie; Moser, Philipp T.; Guyette, Jacques P.; Ren, Xi; Cetrulo, Curtis L.; Leonard, David A.; Fernandez, Leopoldo; Fagan, Shawn P.; Ott, Harald C.
Abstract: The loss of an extremity is a disastrous injury with tremendous impact on a patient's life. Current mechanical prostheses are technically highly sophisticated, but only partially replace physiologic function and aesthetic appearance. As a biologic alternative, approximately 70 patients have undergone allogeneic hand transplantation to date worldwide. While outcomes are favorable, risks and side effects of transplantation and long-term immunosuppression pose a significant ethical dilemma. An autologous, bio-artificial graft based on native extracellular matrix and patient derived cells could be produced on demand and would not require immunosuppression after transplantation. To create such a graft, we decellularized rat and primate forearms by detergent perfusion and yielded acellular scaffolds with preserved composite architecture. We then repopulated muscle and vasculature with cells of appropriate phenotypes, and matured the composite tissue in a perfusion bioreactor under electrical stimulation in vitro . After confirmation of composite tissue formation, we transplanted the resulting bio-composite grafts to confirm perfusion in vivo .